PARENTAL BEREAVEMENT: EXPERIENCES OF THE NURSING STAFF IN NEONATAL INTENSIVE CARE - Luciana de Carvalho Pires; Regina Gema Santini Costenaro; Maria Helena Gehlen; Liliane Alves Pereira; Camila Freitas Hausen; Eliane Tatsch Neves (Cogitare Enfermagem, 2023)
Objective: to know the experience of the nursing team when acting in situations of parental bereavement in Neonatal Intensive Care.